2021
DOI: 10.20944/preprints202111.0372.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sustainable Urban Farming in Sub-Saharan Africa: A Review of a Coupled Single-Loop Aquaponics System in Nigeria

Abstract: Countries in West Africa are adversely affected by climate change (erratic rainfall and rising temperature) resulting in floods, desertification, drought and sea level rise. These events are anticipated to have negative impacts on agricultural development on the continent, ultimately, contributing to food insecurity and environmental degradation. This implies that the production capacity of agrarian communities is unable to meet the food demand of the growing urban population. Can sustainable and innovative ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The grow out weight of the African Catfish at this stocking density at the end of the four months period was above 500 grams and a length above 40 cm. Benjamin et al [6,7] also found that after four months a length of 40 cm as well as a weight of over 500 grams was achievable in African Catfish. Brummet [10] argue that for aquaculture to develop in Africa and provide diverse benefits to society, a business approach that focuses on small and medium scale enterprises must be adopted.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The grow out weight of the African Catfish at this stocking density at the end of the four months period was above 500 grams and a length above 40 cm. Benjamin et al [6,7] also found that after four months a length of 40 cm as well as a weight of over 500 grams was achievable in African Catfish. Brummet [10] argue that for aquaculture to develop in Africa and provide diverse benefits to society, a business approach that focuses on small and medium scale enterprises must be adopted.…”
Section: Discussionmentioning
confidence: 98%
“…A number of factors ranging from high fertility rates to rural-urban migration drives population growth and urbanization [1,41]. This implies that there will be a substantial increase in the demand for animal sourced foods (ASF), specifically fish protein, in cities and towns, which (rural) producers will be unable to meet [7]. Furthermore, prospective (rural) fish farmers, often young and agile, seek greener pastures in cities abandoning farming altogether.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaponics, producing at the same time vegetables and high nutrition value fishes, are considered as sustainable and intensive food production systems. 98,[107][108][109] During recent years, aquaponics technology features and design have evolved to enable its rapid transition to industrialscale production in many nations worldwide, but its uptake in Africa remains relatively limited. Despite the potential advantages of aquaponics in Africa, barriers to its widespread adoption include a lack of technical knowledge, inadequate infrastructure, and lack of funding.…”
Section: Energy Irrigation Nexusmentioning
confidence: 99%
“…The electrical consumption is also considered as the second most cost-intensive component category in aquaponic systems as it covers the requirements of heating and cooling systems as well as operation components (pumps, fans, inverters…). 109,112 For this reason and in order to reduce water heating energy expenses, it is recommended to match the choice of the plants and/or the fishes with the local environmental conditions, particularly ambient air temperature, and to use passive techniques of water heating either directly by a residual heat or by solar energy or by installing soilless units inside greenhouses. 98,102,104,113 Alternatively, fossil fuel electricity can be substituted with photovoltaic electricity to feed aquaponic and hydroponic systems, which improves the energy efficiency of these WEFE nexus solutions.…”
Section: Energy Irrigation Nexusmentioning
confidence: 99%